PENGARUH FLEKSIBILITAS BUDAYA DAN KERANGKA LEVERS OF CONTROL TERHADAP KINERJA PERUSAHAAN - Handayani, Ani; Bastian, Elvin (Pascasarjana Universitas Sultan Ageng Tirtayas, 2017)
This study aims to examine the effect of CF and LOCÂ framework on the performance of companies in manufacturing companies in Banten Province. The population in this study were all manufacturing companies in Banten with the middle managers' unit of analysis. The sample in this research is middle managers (finance, production, HRD, sales and marketing) who have experience in the position for at least 3 years and willing to be respondent in this research. Sampling method used in this research is purposive sampling. The data in this study were obtained by sending questionnaires directly to the respondents, 120 questionnaires were distributed to respondents but only 68 questionnaires that were returned.Â Data in this study were analyzed using Structural Equation Modeling (SEM) method with Partial Least Square approach (PLS). The results of this study showed that CF has significant effect on Belief System, DCS, ICS and CP. In addition, DCS have a significant effect on CP and ICS. However, CF has no effect on boundary systems. Belief Systems and boundary systems are unable to mediate CF on CP. DCS and ICS has a significant positive on CP. boundary system has no effect on CP and Belief System has no effect on CP.Keywords: Cultural Flexibility (CF), Levers Of Control (LOC), Diagnostic Control System (DCS) Company Performance (CP), Interactive Control System (ICS)